Impact of Demonstration and Animation Videos in Flipped Classroom on Chemistry Students’ Performance - Oluwole Caleb Falode; Ibrahim Abba Mohammed; Glory Thomas; Abdulsalam Ovidi Yusuf (Journal of Computers for Science and Mathematics Learning, 2026)
The persistent underperformance of chemistry students in Nigeria remains a growing concern among educators and policymakers. This challenge is largely driven by the subject’s conceptually demanding nature and educators’ limited adoption of technology-driven instructional approaches, even as chemistry continues to underpin critical sectors such as medicine, engineering, and national development. Against this background, this study examined how the use of demonstration and animation videos within flipped classroom environments affects students’ academic outcomes in Niger State, Nigeria. Specifically, the study assessed the impact of these instructional approaches on students’ achievement scores, retention, and attitude toward chemistry. We used a pre-test post-test quasi-experimental design and purposively sampled 144 students from three intact classes in three schools. Descriptive statistics were employed to address the research questions, while Analysis of Covariance, Sidak post-hoc comparisons, and independent samples t-test were used to test the stated hypotheses at a 0.05 significance level. The findings showed statistically significant improvements in both achievement (F(2,140) = 49.945, p = 0.000, η² = 0.927) and retention (F(2,140) = 70.083, p = 0.000, η² = 0.859) among students in the flipped classroom groups relative to those taught conventionally. Attitude scores, however, did not differ significantly between the demonstration and animation groups, implying both approaches were equally effective in enhancing positive dispositions toward chemistry. These outcomes point to a compelling need for pedagogical transformation in Nigerian chemistry classrooms, with a shift toward more technology-integrated and learner-centered instructional methods in Nigerian schools.